Microwave radiometry: a new non-invasive method for the detection of vulnerable plaque - Toutouzas, Konstantinos; Synetos, Andreas; Nikolaou, Charalampia; Stathogiannis, Konstantinos; Tsiamis, Eleftherios; Stefanadis, Christodoulos (Cardiovascular Diagnosis and Therapy, 2012)
Atherosclerosis and its consequences are the most rapidly growing vascular pathology, with myocardial infarction and ischemic cerebrovascular accident to remain a major cause of premature morbidity and death. In order to detect the morphological and functional characteristics of the vulnerable plaques, new imaging modalities have been developed. Intravascular thermography (IVT) is an invasive method, which provides information on the identification of the high-risk atheromatic plaques in coronary arteries. However, the invasive character of IVT excludes the method from primary prevention. Microwave radiometry (MR) is a new non-invasive method, which detects with high accuracy relative changes of temperature in human tissues whereas this thermal heterogeneity is indicative of inflammatory atherosclerotic plaque. Both experimental and clinical studies have proved the effectiveness of MR in detecting vulnerable plaque whereas recent studies have also revealed its association with plaque neoangiogenesis as assessed by contrast enhanced carotid ultrasound (CEUS).